The PORTRAYAL OF THE LATE VICTORIAN UPPER-MIDDLE-CLASS DAUGHTER IN R. N. CAREY’S FOR LILIAS - Alina PINTILII (ACROSS)
Rosa Nouchette Carey is one of the forgotten Victorian female writers who have received some attention lately, as certain modern scholars have attempted to revive her works. Since the latter were chiefly discredited by many late-nineteenth-century critics on account of their genre and commitment to the domestic ideology, these scholars concentrated on proving that domestic fiction was unfairly dismissed and that, despite Carey’s adherence to domesticity, her novels are characterised by an ambivalent attitude towards the traditional domestic ideal and may be regarded as proto-feminist writings. Aiming at reappraising Rosa Nouchette Carey’s works in a more favourable light, the present article also intends to demonstrate that the traditional ideal of domesticity is both supported and challenged within the same novel by comparing the daughter figure represented by the heroine of For Lilias with the idealised expectations the domestic ideology ascribed to girls and by identifying the similarities between the filial image of the novel and the late Victorian model of femininity. Moreover, this paper sets side by side the fictional and socio-historical constructs of the late Victorian upper-middle-class daughter, indicating that the characters in For Lilias and their relationships are not created to mimetically reproduce the social, outside the text, reality, but apparently to reveal some preoccupations of the late nineteenth-century English middle classes, whose ideological context the novel reflects to a large extent.